Adherence to PAP and Subspecialist Referral for PAP Intolerance Following Polysomnogram. (2nd September 2014) - Russell, Jonathon O.; Gales, Jordan; Bae, Charles; Kominsky, Alan
Abstract : Objectives: Obstructive sleep apnea (OSA) is a serious medical condition that adds to patient morbidity and mortality. While treatment with positive airway pressure (PAP) is the standard of care, a significant portion of patients fail to adhere. Little is known about the subsequent management of patients who have refused or failed continuous positive airway pressure. We sought to identify rates of acceptance and adherence to PAP, as well as management and referral patterns of those who failed. Methods: Retrospective cohort study in an academic hospital. All patients undergoing polysomnogram at a single institution during the months of March and April 2010 (n = 1174) were screened for OSA. Adult patients with apnea‐hypopnea index (AHI) > 15 or 5 < AHI < 15 as well as Epworth Sleepiness Scale (ESS) >10 were included for subsequent analysis. Patients undergoing polysomnography were screened for OSA retrospectively using the electronic medical record (EMR). The subsequent management history including tolerance of PAP and referral to specialists upon failure was collected. Results: Of 1174 patients screened, 566 met inclusion criteria. Of 416 patients (74%) with follow‐up information, 237 (57%) were ultimately adherent to PAP. Of 205 nonadherent patients, 86 had refused PAP immediately (42%). Sixty‐one (30%) were referred upon failure or refusal. A total of 139 patients (68%) suffered from untreated OSA without referral to a specialist during a 3‐year follow‐up. Conclusions: Despite the known sequellae of OSA, clinicians are neither treating nor referring a significant percentage of patients with OSA. Therapies other than PAP may be warranted in this population.